Profile of Closed Globe Injury in a Secondary Eye Hospital - Godar, Manita Sunam; Patel, Sushila; Gamal, Nita Sunam; Manandhar, Laxmi Devi (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Closed globe injury of the eye is the type of injury in which the eyewall (sclera and cornea) is intact or only partial thickness wound is present. Studies focused only on closed globe injury of eye are limited. So the aim of the study was to analyse the demographic pattern, modes of trauma, place of trauma, agent of trauma and impact of trauma in different ocular structures and in vision. MATERIAL AND METHODS It was a retrospective, descriptive, cross-sectional study. Details of 167 patients with closed globe injury attending Dr.Binod Neeta Kandel Eye Hospital, Nawalparasi from Aug 2017 to July 2018 were reviewed. Demographic proﬁle, detailed history and examination ﬁndings were analysed. RESULTS Closed globe injury was more common in males (61.7%) than females (38.3%). The mean age was 30.76 ± 16.58 yrs, youngest being 3 years old whereas oldest 90 years old. Left eye was more involved. Domestic accident (38.92%) was the commonest. Conjunctival laceration (21.55%) and traumatic uveitis (21.55%) were the commonest sequelae of closed globe injury. Good vision (Visual acuity (VA) 6/6 -6/18) was seen in 79.64% cases whereas 7.78% cases were blind (VA less than 3/60). CONCLUSION Closed globe injury can occur from different modes of trauma. Anterior segment of eye was more involved than the posterior segment. Even a trivial ocular trauma can have a sight threatening impact.